Trade Policy Implications of Global Value Chains Case Studies - Miroudot, Sébastien (OECD Trade Policy Papers, 2013)
Taking global value chains (GVCs) into account has important implications for trade policy. When production is vertically fragmented and trade in intermediate inputs is prevalent, one has to look differently at a certain number of issues. Through case studies, this paper provides new evidence on the incidence on services of tariffs levied on goods (case study 1) and then discusses effective rates of protection in a world of GVCs and what the removal of tariffs on intermediate inputs implies, using the example of Canada (case study 2). To illustrate how trade agreements could be made more relevant for GVCs, the paper further looks at sectoral approaches in trade negotiations through the example of the Information Technology Agreement (case study 3) and finally compares the network of regional trade agreements in force with global production networks (case study 4)